PENGARUH SAMPAH DEDAUAN TERHADAP KEPADATAN POPULASI SERANGGA TANAH KECAMATAN MAULAFA NUSA TENGGARA TIMUR - Merlinda Seftiani Detista Bili; Paulus Taek; Mario J. Santru (SINERGI : Jurnal Riset Ilmiah, 2026)
Soil fauna play a crucial ecological role in maintaining ecosystem balance, particularly in litter decomposition, soil structure improvement, and nutrient cycling. However, the presence of toxic chemical residues from leaves and herbicide applications has the potential to disrupt the survival of soil fauna. One source of litter suspected of impacting soil fauna is Chromolaena odorata, a weed containing bioactive flavonoids, alkaloids, tannins, and saponins. This study aimed to determine the effect of leaf litter on soil insect populations and to analyze the impact of certain types of leaf litter in Maulafa District, East Nusa Tenggara. The study was conducted in November 2024 on cultivated land sprayed with Roundup herbicide in Maulafa Village, Kupang City. The research methods included soil and litter sampling, measuring pH, temperature, and soil moisture, and collecting soil fauna using the zigzag method in a 10 × 10 m plot at depths of 5, 10, and 15 cm. Samples were extracted using a modified Tullgren funnel for 24 hours and identified to the family or species level. The results of the study showed that 16 orders/families/species of soil fauna were found that generally live in the litter layer, while Isotomidae, Onychiuridae, and Sminthuridae are able to live up to a depth of 5 cm. Leaf litter acts as a source of energy and nutrition for soil fauna, and the chemical compounds of Chromolaena odorata are not lethal because soil fauna have an internal detoxification mechanism.